1089 Visual Evoked Potentials in Term and Preterm Infants. (October 2012) - Brackmann, F; Scheu, S; Trollmann, R
Abstract : Background and Aims: Evoked potentials are a useful non-invasive method for the assessment of neurological status in term and preterm infants at risk for perinatal CNS damage. The present study intended to gather reference values of visual evoked potentials (VEP) for preterm and term neonates and identify neonates at risk for perinatal CNS lesions using VEPs. Methods: 23 healthy preterm and term neonates (group A) and 16 infants with perinatal brain injury (group B) were examined for this study. Groups were classified according to their post-conceptual age (A1/B1: 42–45 weeks, n=4/6; A2/B2: 38–41 weeks, n=5/8; A3: 36–37 weeks, n=12; A4/B3: < 36 weeks, n=2/2). Stimulation was triggered by stroboscopic flashes (1 Hz/10 µs) and P1 and N2 waves were analyzed. Results: Latencies significantly correlated with post-conceptual age (P1: p<0.001, N2: p<0.05) and gestational age (P1: p<0.01). The average latency values (mean±SD) of the subgroups were: group A1 (P1:165.7ms±33.5; N2:211.5ms±29.9), A2 (P1: 199.6ms±34.2; N2:255.6ms±25.8), A3 (P1:223.8ms±14.7; N2:272.1ms±13.5), A4 (P1:240 resp. 209ms; N2:242 resp. 233ms). Average latencies of term infants with or without perinatal injury differed significantly for P1 (228.8 ms±30.9 vs. 165.7ms±33.5; p<0.05) and N2 (266.0 ms±21.1 vs. 211.5ms±29.9; p<0.01). Conclusions: The present study adds to the knowledge on normal VEP values during early development. Present data showed a negative correlation with post-conceptual age for central latencies as an equivalent of progressing myelination regardless of extra- or intrauterine maturation. Term infants with perinatal brain injury showed significantly prolonged VEP latencies compared to healthy children.